The Effects of Aerobic Exercise on Body Image Attitudes in Women - Sareh Zar-Shenas; Ashraf Karbalaaei-Nouri; Seyyed-Ali Hosseini; Mahdi Rahgozar; Reza Seyed-Nour; Nahaleh Moshtagh (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: Sociocultural emphasis and increased interest in physical attractiveness and current attitudes body structure have increased body image dissatisfaction among women. The prevalence of body image dissatisfaction is linked with various psychological disorders and disturbances such as low self-esteem, depression and other disorders. The present study investigated the short program aerobic exercise effects on body image among women. Materials & Methods: In this interventional and quasi experimental study, 82 females among 150 women (18-45 years old) referred to Enghelab and Gol sports clubs in Tehran were selected by convenient and simple sampling based on inclusive and exclusive criteria and randomly divided into two intervention and control groups. They did not participate in any exercise in last 3 months and also they did not have any physical disease and meet criteria for deficit of body image attitudes. Data collection was done by using demographic and Multidimensional Body Self-Relation Questionnaire. The intervention group participated in aerobic exercise program. These sessions lasted 3 hours per week for 4 weeks. Data were analyzed by Chi-Square, Paired T and Independent T tests. Results: There were significant differences between two groups after intervention in sub items of body image including: self-appearance evaluation (P<0.001), self-appearance orientation (P<0.001), health orientation (P=0.003), illness orientation (P=0.002), but their fitness evaluation (P=0.141), self-fitness orientation (P=0.888), health evaluation (P=0.072), self-body satisfaction (P=0.082), overweight preoccupations (P=0.167) and self-assesed weight (P=0.156) did not change clearly. Conclusion: Short periods of aerobic exercise can effectively promote body image attitudes among women, and exercise can be used as a method of treatment in occupational therapy of the disorder.